The School Leadership Preparation Project: A Multi-Case Study on Education Policy in South Sulawesi Province - Ardiansyah, Muhammad; Arismunandar,; Ansar,; Faridah, (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This research investigates the School Leadership Preparation Project in South Sulawesi Province. The project consists of a series of activities designed to identify highly potential and experienced teachers who are prepared to take on additional responsibilities as school principals. The process involves two stages: (1) selection (comprising administrative and academic selection), and (2) education and training. This study critically examines the policy formulation, its implementation, and the outcomes in South Sulawesi Province. Data collection was conducted through participatory observation, in-depth interviews, and document analysis. The individual data analysis followed the Miles and Huberman (2014) flow model, which includes data condensation, data display, and conclusion drawing/verification. For cross-case analysis, a comparative approach was employed as recommended by Yin (2002). The findings indicate that the School Leadership Preparation Project is more responsive to current needs than to future demands, as the political discretion of local leaders often outweighs adherence to central government policies. Moreover, the project is primarily attended by junior or low-tenure teachers, who may lack the leadership qualifications expected of prospective school leaders. The content of the school leadership preparation programs focuses more on leadership development rather than on managerial skills, school entrepreneurship, or educational supervision. Abstrak: Penelitian ini menyelidiki Proyek Persiapan Kepemimpinan Sekolah di Provinsi Sulawesi Selatan. Proyek ini terdiri dari serangkaian kegiatan yang dirancang untuk mengidentifikasi guru-guru yang berpotensi dan berpengalaman yang siap untuk mengambil tanggung jawab tambahan sebagai kepala sekolah. Prosesnya meliputi dua tahap: (1) seleksi (terdiri dari seleksi administrasi dan akademik), dan (2) pendidikan dan pelatihan. Kajian ini mengkaji secara kritis perumusan kebijakan, implementasinya, dan outcome di Provinsi Sulawesi Selatan. Pengumpulan data dilakukan melalui observasi partisipatif, wawancara mendalam, dan analisis dokumen. Analisis data individu mengikuti model aliran Miles dan Huberman (2014), yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan/verifikasi. Untuk analisis lintas kasus, pendekatan komparatif digunakan seperti yang direkomendasikan oleh Yin (2002). Temuan-temuan yang ada menunjukkan bahwa Proyek Persiapan Kepemimpinan Sekolah lebih responsif terhadap kebutuhan saat ini dibandingkan tuntutan di masa depan, karena kebijaksanaan politik para pemimpin daerah seringkali melebihi kepatuhan terhadap kebijakan pemerintah pusat. Selain itu, proyek ini sebagian besar diikuti oleh guru-guru junior atau guru dengan masa jabatan rendah, yang mungkin tidak memiliki kualifikasi kepemimpinan yang diharapkan dari calon pemimpin sekolah. Isi program persiapan kepemimpinan sekolah lebih menitikberatkan pada pengembangan kepemimpinan dibandingkan keterampilan manajerial, kewirausahaan sekolah, atau supervisi pendidikan.